Detection of Rubella Antibodies in Women with Repeated Miscarriage During Different Seasons in Mosul City - Karam Aldabbagh (University of Mosul, 2022)
Background: Rubella or German measles is a viral disease transmitted via aerosol droplets affecting mainly children, Mostly, rubella is a simple and self-limiting disease with no chronic consequences, except in infected pregnant women which may result in devastating outcomes depending on the trimester of pregnancy. Materials and methods: the study enrolled 1004 women suffering from spontaneous miscarriage tested for rubella IgM antibodies using ELISA. The sampling was conducted in two different seasons, summer and winter. Results: Test reading showed that 15.23% of all tested women were positive for rubella IgM antibodies i.e. 153 out of 1004 women. Seasonal change showed no significant variation in the percentage of the infection, where 15.8% of all participants were positive in summer versus 14.35% seropositive in the winter season (p˃ 0.05). Conclusion: Rubella infection is affecting a relatively high number of women suffering from a spontaneous miscarriage in Mosul city, and there was no seasonal variation in the rate of infection.